The Effect of Leg Muscle Weight Training and Shuttle Drill Kick on The Speed of Pencak Silat Sickle Kick - Surya Janwar Maulana; Indra Safari; Muhammad Nur Alif (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study was conducted to determine the effect of Weight Training leg muscle exercises and Shuttle Drill Kick on the speed of the sickle kick of extracurricular Pencak Silat Tapak Suci athletes at Junior High School Muhammadiyah Majalaya, the sample used a Saturated sampling technique and the sample taken was 20 people. This study used quantitative with an experimental method with a two group Pretest-Posttest design. The instrument used in this study was a sickle test. The results of data management were calculated to see the effect of Weight Training leg muscle exercises and Shuttle Drill Kick on the speed of the sickle kick of extracurricular Pencak Silat Tapak Suci athletes at Junior High School Muhammadiyah Majalaya. With the results of Weight Training for the right leg having an effect of 68.7%, for the left leg 64.0%. while the results of the Shuttle Drill Kick for the right leg had an effect of 86.0%, for the left leg 66.9%. This means that weight training leg muscles and shuttle drill kick can increase the speed of the sickle kick.